Toward the production of milk-identical proteins using precision fermentation on agricultural waste substrates : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biological Sciences at Massey University, Albany, New Zealand - McIsaac, Emily Claire (Massey University, 2023)
Animal farming is responsible for a considerable portion of global greenhouse gas emissions. Decreasing carbon production from this source would thus slow the progress of global warming. In addition, treaties such as The Paris Agreement stipulate that there must be a global drive toward carbon neutrality. Novel food production methods must be explored to decrease carbon emissions associated with animal farming, ranging from milk production to meat production. Recombinant protein expression and precision fermentation are gaining popularity as potential options for producing food proteins such as bovine milk proteins. Bovine milk constitutes a staple part of global diets, and demand is increasing. However, the current method of dairy farming is a resource-heavy and environmentally damaging process. Precision fermentation to produce bovine identical milk proteins could usher in a new era of food production that steers the dairy industry towards an economical and environmentally friendly future. In this study, we explore the production of bovine milk proteins from microbial hosts as a potential source of consumable proteins. We use a protease-deficient strain of Escherichia coli (E. coli) BL21 (De3) as a microbial host to express casein, the dominant protein in cow's milk. Additionally, we investigate common agricultural waste substrates as food sources for host organisms. We aim to determine the most efficient carbon source for maximum microbial growth sourced from an existing industry, redirecting waste from landfills.
Keywords: 300103 Agricultural molecular engineering of nucleic acids and proteins